HYPOCENTER DETERMINATION AND CLUSTERING OF VOLCANO-TECTONIC EARTHQUAKES IN GEDE VOLCANO 2015 - Nugraha, Aulia Kharisma; Maryanto, Sukir; Triastuty, Hetty (Jurnal Neutrino, 2017)
Gede volcano is an active volcano in West Java, Indonesia.  Research about determination the volcano-tectonic earthquake source positions has given results using volcano-tectonic earthquakes data from January until November 2015. Volcano-tectonic earthquakes contained deep (VT-A) have frequency (maximum amplitude) range 5 – 15 Hz. Furthermore, they contain shallow earthquake, VT-B have range 3-5 Hz and LF have range 1-3 Hz. Geiger’s Adaptive Damping (GAD) methods used for determining the hypocenter of these volcano-tectonic (VT) events. Hypocenter distribution divided into 4 clusters. Cluster I located in the crater of Gede volcano dominated by VT-B earthquakes their depth range 2 km below MSL to 2 km above MSL including the VT-B swarm. The seismic sources in cluster I indicated dominant due to the volcanic fluid or gas filled in conduit pipes. Cluster II located at the west of Gede volcano caused by Gede-Pangrango fault-line dominated by VT-A earthquakes with depths range 1.5 km below MSL to 700 m above MSL. Cluster III located in the North of Gede volcano dominated by VT-A events there caused by graben fault area with those depths range 7.5 – 1.65 km below MSL. Cluster IV located in South West of Gede volcano contained VT-A earthquakes with depth range at 10 km below MSL and VT-B earthquakes this depth 2 km below MSL. Due to magma intrusion filled into fractures of the fault in the West of Gede volcano this shallow magma filling-fractures and degassing in subsurface assumed dominates the volcano-tectonic events from January to November 2015 due to faults extends from North to South occured in the West of Gede volcano.